Transcatheter mitral valve replacement in native mitral valve with severe mitral annular calcification: Skirting the Sapien 3 to reduce the risk of paravalvular leaks - Pozzoli, Alberto; Torre, Tiziano; Pedrazzini, Giovanni; Demertzis, Stefanos; Ferrari, Enrico (Frontiers in Cardiovascular Medicine, 2022)
Background Mitral annular calcification (MAC) may represent a major challenge for heart surgeons during mitral valve (MV) surgery, with an extremely high perioperative risk. The risk is further increased when patients fail to be eligible for any percutaeous treatment, in particular because circumferential calcifications involving the anterior leaflet suggest a critical obstruction of the left ventricular outflow tract (LVOT). Methods Since 2020, 5 high-risk patients (mean age 70 years, 63-76; 4 females) with severe mitral disease in the context of severe MAC (computed tomography-based mean MAC Score 8.2±1.1) were operated on adopting this novel technique. The operations were performed under general anesthesia, using a transapical TAVI delivery system to position the Sapien 3 in mitral position, under direct vision. In detail, to reinforce and prevent the implant from paravalvular leakages, it was previously sewn a pericardial skirt around the prosthesis, fixing it to the annulus and to the perivalvular atrial surface. Results Sapien 3 Ultra implantation was successful with absence of residual MR in all 5 patients (mild paravalvular leak in 1 case). Four patients were implanted a 29 mm valve and one a 26 mm. Predilatation of the native annulus was never performed. Perfusion and clamping times were 134±53 mins and 108±43 mins, respectively. The presence of the pericardial skirt reduced the risk of leakage between the prosthesis and the rigid calcium surface, with final mean and maximal gradients of the TAVI prosthesis of 4.1 and 10.8 mmHg, respectively. There were no left ventricular outflow tract obstructions (mean LVOT gradient 8±1 mmHg). All patients were discharged and neither mortality, nor prosthetic dysfunction and residual mitral regurgitation were recorded. During follow-up, the last patient treated (MAC Score 10) returned to our attention with a significant recurrent jet originating from the anterolateral commissure, currently medically treated given the prohibitive redo risk. Conclusion Direct open surgical implantation of Sapien 3 valve can be safely done in patients with severe MAC, in experienced centres. Reinforcing the TAVI prosthesis by sewing a pericardial skirt led to very satisfactory perioperative and early post-operative results, reducing paravalvular leakages. Complex anatomies are at high-risk of recurrence.